Analisis Pola Operasi Lalu Lintas Kereta Api Pada Stasiun Berjalur Empat dan Enam dengan Metode Conflict Rate (Politeknik Perkeretaapian Indonesia Madiun, 2022)
The Sembawa-Betung double rail track is one of the planned routes of the Trans Sumatra Railways project in Sumatra Island dedicated to passenger and goods transportation. This study aims to analyze the train operating systems of Sembawa - Betung double rail track, that consist of the effective length and the typical layout of rail track, train traffic management, the potential of train travel routes that can be formed, used and conflicted, and the calculation of routes loading level on the train frequency. Based on the analysis conducted using the Conflict Rate method, it can be summarized that the route utilization along with trains frequency served at Sembawa Station, Pangkalan Balai Station and Suak Tapeh Station almost reaches the maximum level of allowable conflict so it may increase the probability of train accidents if there is an additional number of trains served without the construction of additional rail track at the station. On another side, the route utilization, along with the frequency of the trains served at Betung Station, is still far below the maximum limit of allowable conflict, so that there is a possibility to increase the frequency of the trains without the need for additional rail track at the station.